On the production of victory: empirical determinants of battlefield success in modern war - Rotte, Ralph; Schmidt, Christoph M. (Discussion paper series, 2002)
Using a data set of historical battles from 1600 to 1973, this paper analyzes the empirical determinants of tactical success in modern war. Based on a reduced form approach we consider key elements of military theory as factors in the production of combat success, formalized in a military production function. The paper focuses on the relationship of material and non-material factors to battlefield success, and especially on the role of superior force strengths. Contrary to the emphasis on technology which can be found in the recent literature, our estimation results indicate that numerical superiority has retained its crucial role for battlefield performance throughout history. In general, human elements of warfare, like leadership, morale and surprise, have continued to be important determinants of battle outcome despite technological progress in weapons.